APAKAH KEPUTUSAN PERUSAHAAN MELALUI PENGGUNAAN UKURAN PERUSHAAN DAPAT MENINGKATKAN NILAI PERUSAHAAN? - Maulana, M. Ikhsan; Ikhsan, Syarbini; Umyana, Ayu (AKUNTANSI DEWANTARA, 2024)
The purpose of this quantitative research is to determine the impact of capital structure, earnings per share, and dividend policy on firm value and whether firm size can act as a moderating factor. The secondary data used is annual report data covering the years 2019-2022. 25 palm oil or CPO issuers listed on the Indonesia Stock Exchange became the population of this study. Purposive sampling with certain criteria is used in the sampling approach to obtain eight companies that meet the criteria. Moderation regression analysis, multiple linear analysis, and classical assumption tests were used in this research technique. Microsoft Excel and EViews 10 were used as analytical tools. The research findings show that, in contrast to dividend policy and capital structure which have no significant effect on firm value, earnings per share has a considerable impact on firm value. The impact of capital structure, earnings per share, and dividend policy on firm value cannot be mitigated by firm size.